Manipulate the first equation to
y = 22-7z
Then substitute in the second to find z
8(22-7z) + 7z = 127
176-56z+7z = 127
-49z = -49
z = 1
So y = 22-7(1) = 22-7 = 15
y = 15; z = 1
Answer:
2(4a - 4b) + 4(3a + 2b) = 20a
Step-by-step explanation:
2(4a - 4b) + 4(3a + 2b)
8a - 8b + 12a + 8b
8a + 12b - 8b + 8b
20a+ 0 = 20a
Thus, 2(4a - 4b) + 4(3a + 2b) = 20a
<u>-TheUnknownScientist</u>
Answer:4
Step-by-step explanation: please just trust me!
Answer:
D
Step-by-step explanation:
Answer: slope= -3,5
Step-by-step explanation: